Lock and unlock of the nation during pandemic waves: a cross-sectional study observing the spread of COVID -19 in India - Presthiena Lofi; A B Prasad; P R Varghese; Praveenlal Kuttichira (Shahid Beheshti University of Medical Sciences, 2022)
Background:  The lockdown policies and pandemic curve in India during the two overlapping waves were different. This study aimed to explore the spread of COVID-19 pandemic transmission during the first and second waves in the context of nationwide lockdown in India. Methods: The present study was a cross-sectional analysis of the COVID-19 incidence and daily fatalities from March 24, 2020 to July 17, 2021 was done using data retrieved from public domains of governmental websites and COVID-19 dashboards.  The daily number of cases (DNC), and the daily number of deaths were observed in the context of the lock and unlock phases and analyzed using descriptive statistics in Microsoft Excel 2010. Results: The country was able to effectively handle the first wave in 2020, delaying the peak by up to six months, in which nationwide lock down probably had an effect. During the first pandemic wave in 2020, the DNC increased from 506 cases on March 23 (Lock 1) to a peak of 97,874 cases on September 16 (Unlock 4), before declining to 31,118 cases on November 30 (Unlock 6) as the lockdown came to an end.  With only state-level lockdowns in the second wave, the DNC jumped from 9,121 cases on 15th February 2021 to 414,118 cases on May 6, 2021 and then dropped to 30,093 cases on July 19, 2021. The peak was uncontrollable, with 1,846,806 cases and 236,529 deaths reported across the country in the three months from April 1 to June 30, 2021. Conclusion: The nationwide lockdown probably had an effect on the control of pandemic during the first wave. The findings highlighted the desirability of national policies, and synchronization of lockdown restrictions across the country during pandemic.